Correlation analysis between multifidus muscle atrophy and the severity of degenerative scoliosis retrospective, cross-sectional study - Jiangkai Yu; Cong Zhang; Yan Zhou; Jing Wang; Youheng Zhang; Yuntao Wang (Scientific Reports)
Abstract Degenerative scoliosis (DS) is a significant health concern, affecting approximately 32–68% of the Chinese population aged 65 and above. This study aims to investigate the correlation between multifidus muscle atrophy and the severity of spinal curvature in DS patients, thereby providing evidence-based recommendations for the clinical prevention and management of DS. After applying the inclusion and exclusion criteria, 231 patients with chronic low back pain admitted to the Department of Spinal Surgery, Zhongda Hospital affiliated with Southeast University between January 2023 and January 2024 were ultimately selected as the study population. Based on imaging diagnosis, chronic low back pain patients without DS were assigned to the control group (non-DS, n = 81), while patients with scoliosis were assigned to the observation group (DS, n = 150). The observation group was further subdivided into mild scoliosis (n = 72), moderate scoliosis (n = 56), and severe scoliosis (n = 22) groups based on the degree of curvature. ImageJ software was used to measure the cross-sectional area (CSA) of the multifidus muscle at the mid-level of L4 and L5 on T2-weighted magnetic resonance imaging (MRI) scans and calculate the degree of atrophy. The proportion of males and bone mineral density (BMD) were significantly higher in the non-DS group compared to the DS group (P < 0.05). The multifidus cross-sectional area (CSA) and functional cross-sectional area ratio (LCSA/GCSA) were significantly higher in the non-DS group than in the DS group (P < 0.05). Patients in the severe scoliosis group were significantly older than those in the mild and moderate groups, and had significantly lower BMD than the mild group (P < 0.05). The LCSA/GCSA was highest in the mild scoliosis group, lowest in the severe scoliosis group, and intermediate in the moderate group (P < 0.05). CSA was significantly higher in the mild scoliosis group than in the severe group (P < 0.05). In the mild and moderate scoliosis groups, the convex-side CSA and LCSA/GCSA were significantly greater than those on the concave side (P < 0.001). In the severe scoliosis group, no significant difference was found in convex-side versus concave-side CSA (P = 0.307), but convex-side LCSA/GCSA remained significantly greater than concave-side (P = 0.007). Pearson correlation and linear regression analysis showed no correlation between multifidus LCSA/GCSA and Cobb angle in non-DS patients (P > 0.05), but a significant negative correlation existed in DS patients (P < 0.05). The absolute value of the correlation coefficient increased with worsening scoliosis severity (severe group > moderate group > mild group). Multifidus muscle atrophy is closely associated with degenerative scoliosis. Multifidus LCSA/GCSA negatively correlates with scoliosis severity in DS patients, but not in non-DS patients. The convex side exhibits less atrophy compared to the concave side in DS patients. The difference in concave-convex sides is more pronounced in patients with mild to moderate conditions. Increasing age and reduced BMD may be associated with worsening scoliosis severity. When BMD <  − 0.900 T-Score, LCSA/GCSA < 0.805, and the patient is female, the likelihood of developing DS is high.